2012
DOI: 10.5713/ajas.2012.12023
|View full text |Cite
|
Sign up to set email alerts
|

Increases of Antibiotic Resistance in Excessive Use of Antibiotics in Smallholder Dairy Farms in Northern Thailand

Abstract: Antibiotic resistance patterns of bacterial isolates from both quarter teat-tip swabs and their quarter milk samples were evaluated in smallholder dairy farms in northern Thailand with excessive use of antibiotics (HIGH) compared with normal use (NORM). Results from teat-tip swab samples showed that the percentage of Bacillus spp. resistance to overall antibiotics was significantly lower in the NORM group than that of the HIGH group, whereas, the resistance percentage of coagulase-negative staphylococci in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
1
18
2
2
Order By: Relevance
“…In this study, the highest multi-drug resistance (MDR) was observed to the following antibiotics ampicillin, tetracycline, and trimethoprim/sulfamethoxazole. These findings were in agreement with other studies done in Iran, USA, India, Brazil, Thailand, and Southern African, [1,16,36,[43][44][45] that revealed MDR in Enterobacteriaceae, including Salmonella spp. and E. coli.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the highest multi-drug resistance (MDR) was observed to the following antibiotics ampicillin, tetracycline, and trimethoprim/sulfamethoxazole. These findings were in agreement with other studies done in Iran, USA, India, Brazil, Thailand, and Southern African, [1,16,36,[43][44][45] that revealed MDR in Enterobacteriaceae, including Salmonella spp. and E. coli.…”
Section: Discussionsupporting
confidence: 93%
“…The high antibiotic resistance could be due to indiscriminate and injudicious use of antibiotics, about which there is no authentic data available even for cattle in India. Increased antibiotic usage is known to increase antibiotic resistance among bacteria isolated from cases of mastitis [ 85 ]. Incidentally, considerable amount of antimicrobials are used in India for food animal production, although much of it is probably used in poultry and piggery sectors; in addition, the country is projected to witness a manifold increase in antimicrobial usage in the near future [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus spp. strains are considered the most common pathogen for BM [ 2 ]. In a survey conducted from 2015 to 2017, the isolation rate of Streptococcus spp.…”
Section: Introductionmentioning
confidence: 99%